Christian Religious Education, Testimony, and Technology: A Holistic Approach to Christian Education - Lasmauli Gurning; Maria Titik Windarti (Sekolah Tinggi Teologi Kadesi Bogor, 2023)
This article discusses how technology and testimonies can be integrated into Christian religious education to create a holistic approach that builds character. Testimonies share personal stories about how faith impacts people's lives, while technology enables personalized and interactive learning experiences beyond traditional classrooms. This article emphasizes the importance of using testimonies in Christian education to connect faith with practical life situations. The holistic approach to Christian education aims to develop students comprehensively, including their physical, social, emotional, and spiritual aspects. Strategies and benefits for incorporating technology and testimonies are also discussed, along with approaches for implementing the holistic approach. In conclusion, integrating technology and testimonies in Christian education can improve students' understanding of Christian values and their practical application in everyday life.